Optimization Multi Response on Electrical Discharge Machining Sinking Process Using Taguchi-Grey-Fuzzy Methods - Rahayu Mekar Bisono; Rifky Maulana Yusron (International Journal of Science, Engineering, and Information Technology, 2020)
Electronic Discharge Machining (EDM) sinking applied widely in advance material manufacturing, every process parameter will count on this company. Their performance evaluated by some parameters such as surface roughness and tool wear ratio. Then they will be a dependent variable on this research. Independent variables on this research are electrode polarization, gap voltage, duty factor and pulse current.  Every variable has three levels, except electrode polarization has two levels. This research conducting using Taguchi matrix orthogonal L18 (21×33) methods. The aim of this experiment is to evaluate optimization parameter process on EDM sinking, using Taguchi-Grey-Fuzzy methods. Characteristics response optimal applied are ‘smaller better’ for surface response roughness and tool wear ratio. This research using DAC tool steel as work-piece. DAC is most widely used as die for aluminum and zinc die-casting. The aim of this research is finding contribution of variable in EDM sinking parameter. Result of this research show contribution from variable process to reduce variance total observed response simultaneously, in order are electrode polarization on 49,53%, gap voltage on 23,52%, duty factor on 5,45% and pulse current on 9,92%. From validated optimization in confirmation experiment, to conclude combination variable process optimal response value is electrode polarization on positive, gap voltage at 50V, duty factor at 0.5 and pulse current at 12A.